1994
DOI: 10.1002/jab.770050109
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonated polyurethanes that resist calcification

Abstract: Cardiovascular implant mineralization involving bioprosthetic materials, such as glutaraldehyde cross linked porcine aortic valves or synthetic materials such as polyurethanes, is an important problem that frequently leads to clinical failure of bioprosthetic heart valves, and complicates long‐term experimental artificial heart device implants. Novel, proprietary, calcification resistant polyetherurethanes (PEU) as an alternative to bioprosthetic materials were the subject of these investigations. A series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…[11][12][13][14][15] Our polyurethane bisphosphonate derivatization studies demonstrated that covalent attachment of bisphosphonates effectively inhibited polyurethane mineralization, and had essentially no effect on the biomechanical properties of the polyurethane heart valve leaflets. 9,10,16 In the present studies, we utilized polyurethane films in order to investigate two unique surfaces for use in gene delivery studies: (1) Attaching a collagen coating to the surface of polyurethane films, with subsequent derivatization of the collagen coating with thiol-based attachment of anti-adenovirus antibodies, and (2) using alkyl-thiol-activated polyurethane films to directly attach anti-adenovirus antibodies to the surface of polyurethane surfaces. These thiol-reactive sites were then further reacted in each instance to attach antiadenovirus antibodies for vector tethering.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Our polyurethane bisphosphonate derivatization studies demonstrated that covalent attachment of bisphosphonates effectively inhibited polyurethane mineralization, and had essentially no effect on the biomechanical properties of the polyurethane heart valve leaflets. 9,10,16 In the present studies, we utilized polyurethane films in order to investigate two unique surfaces for use in gene delivery studies: (1) Attaching a collagen coating to the surface of polyurethane films, with subsequent derivatization of the collagen coating with thiol-based attachment of anti-adenovirus antibodies, and (2) using alkyl-thiol-activated polyurethane films to directly attach anti-adenovirus antibodies to the surface of polyurethane surfaces. These thiol-reactive sites were then further reacted in each instance to attach antiadenovirus antibodies for vector tethering.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Similarly, PDMS-based PUs (Elast-Eon, Angioflex, etc) that also contain surface ─O─ atoms (─Si(Me) 2 ─O─Si(Me) 2 ─) are also prone to calcification. 22,28,29 The objectives of our investigations were to assess the calcification resistance of PIB, PIB-based PUs, SIBS, and similar PIB-containing materials containing a reinforcing agent and, further, to compare their calcification resistance with a widely used relatively calcification resistant PDMS-based PU, Elast-Eon (we were unable to obtain Angioflex, another PDMS-based PU developed for calcification resistance, for these studies).…”
Section: Figurementioning
confidence: 99%
“…Conventional polyether‐based PUs (ie, PUs whose continuous soft segment is of polytetramethylene oxide, such as pellethane, tecothane, etc) that contain ether oxygen atoms (─CH 2 ─O─CH 2 ─) at their surfaces are prone to calcification . Similarly, PDMS‐based PUs (Elast‐Eon, Angioflex, etc) that also contain surface ─O─ atoms (─Si(Me) 2 ─O─Si(Me) 2 ─) are also prone to calcification …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of the anti-calcification agents [i.e., polyetherurethanes (PEU) 213 and polyhedral oligomeric silsesquioxane-poly(carbonateurea)urethane (POSS-PCU) 214 ] into polymer matrix significantly reduces calcification without hindering its mechanical properties. The second factor that needs to keep in mind while designing a cardiovascular implant is the thrombosis and intimal hyperplasia.…”
mentioning
confidence: 99%